Esophagojejunostomy after total gastrectomy for caustic injuries. Issue 2 (26th April 2013) - Chirica, M.; Kraemer, A.; Petrascu, E.; Vuarnesson, H.; Pariente, B.; Halimi, B.; Munoz‐Bongrand, N.; Sarfati, E.; Cattan, P.
Summary The objective of the study was to compare outcomes of emergency esophagogastrectomy (EGT) and total gastrectomy with immediate esophagojejunostomy (EJ) in patients with full‐thickness caustic necrosis of the stomach and mild esophageal injuries. After caustic ingestion, optimal management of the esophageal remnant following removal of the necrotic stomach remains a matter of debate. Between 1987 and 2012, 26 patients (men 38%, median age 44 years) with isolated transmural gastric necrosis underwent EGT (n = 14) or EJ (n = 12). Early and long‐term outcomes of both groups were compared. The groups were similar regarding age (P = 0.66), gender (0.24), and severity of esophageal involvement. Functional success was defined as nutritional autonomy after removal of the jejunostomy and tracheotomy tubes. Emergency morbidity (67% vs. 64%, P = 0.80), mortality (17% vs. 7%, P = 0.58), and reoperation rates (25% vs.14%, P = 0.63) were similar after EJ and EGT. One patient (8%) experienced EJ leakage. One patient in the EJ group and 13 patients in the EGT group underwent esophageal reconstruction (P < 0.0001). Aggregate in hospital length of stay was significantly longer in patients who underwent EGT (median 83 [33–201] vs. 36 [10–82] days, P = 0.001). Functional success after EJ and EGT was similar (90% vs.69%, P = 0.34). Immediate EJ can be safely performed after total gastrectomy for caustic injuries and reduces the need of further esophageal reconstruction.